As Time Goes By in Argentina : Economic Opportunities and Challenges of the Demographic Transition - Gragnolati, Michele (Washington, DC: World Bank, 2015)
The process of demographic transition through which Argentina is passing is a window of both opportunities and challenges in economic and social terms. Argentina is still a young country in which the working-age population represents the largest proportion of its total population. Currently, the country just began a 30-year period with the most advantageous age structure of its population, which could favor greater economic growth. This situation, known as the 'demographic window of opportunity,' will last until the beginning of the 2040s. The dynamics of the fertility and mortality rates signify a gradual ageing of the population, with implications for various dimensions of the economy, the social protection system, public policies, and society in general.